Treatment of Tanning Effluent Using Seaweeds and Reduction of Environmental Contamination - V. Sampathkumar; S. Southamirajan; Elango Subramani; Senthilkumar Veerasamy; D. Ambika; Dineshkumar Gopalakrishnan; G. E. Arunkumar; K. Raja; S. Arulmozhi; Dhivya Balamoorthy (Journal of Chemistry)
One of the main sources of dangerous chemicals that are dumped untreated into land and water bodies and have a negative influence on the ecosystem are industrial effluents. Seaweeds are currently used for treating industrial effluent effectively. The technology is at a maturing stage. This paper reviews the characterization and cultivation of seaweeds for wastewater treatment. In this present study, different extracts of four seaweeds such as Gracilaria edulis, Sargassum wightii, Turbinaria ornata, and Kappaphycus alvarezii, from the Mandapam coastal regions were analyzed. The seaweeds are used to treat the leather industry effluents collected from EKM leather processing company, Erode, Tamil Nadu, India. Among all, extracts of Gracilaria edulis survived at different concentrations of TDS: 15,000, 25000, and 35000 mg/l. Out of these different ranges, TDS of about 25000 mg/l seaweed named Gracilaria edulis reduced more amounts of chemicals present in the effluent like TDS (93.90%), phosphates (72.71%), nitrate (75.08%), nitrite (76.92%), and turbidity (99.01%) content. Additionally, we produce the quality and strength of agar gel from the cultivation of Gracilaria edulis by the Nikansui method. Finally, we got the extraction procedure to obtain a higher yield of about 10.26% and a maximum gel strength of 92.06 g·cm−2 while maintaining the melting point at 78°C.